Pop(ping) across the Rhine: The Rise of Subculture in Germany (KULT_online, 2009)
Combining global phenomena with local particularities for scientific purposes is not only promising but also necessary in the realm of cultural studies, given the fact that the focus on a certain issue bears evidence if and only if the production conditions of the analysed phenomena are also taken into consideration. The edited volume Pop in R(h)einkultur. Oberflächenästhetik und Alltagskultur in der Region (Pure Pop on the Rhine: Surface Aesthetics and Everyday Culture in the Region) comprises the talks delivered at the conference of the same name that took place in Düsseldorf in October 2007. Its objective was to establish and to structure, in scientific discourse, the three terms “pop”, “popular culture” and “pop culture” with respect to specific locations. On reading the diverse contributions, it becomes evident that topics related to pop, which go beyond cultural and media science as well as musicology, still require a sound theoretical base.